Thyroid axis participates in high-temperature-induced male sex reversal through its activation by the stress response - Castañeda Cortes, Diana Carolina (2023)
Environmental changes alter the sex fate in about 15% of vertebrate orders, mainly in ectotherms such as fsh and reptiles. However, the efects of temperature changes on the endocrine and molecular processes controlling gonadal sex determination are not fully understood. Here, we provide evidence that thyroid hormones (THs) act as co-players in heat-induced masculinization through interactions with the stress axis to promote testicular development. We frst demonstrated that the thyroid axis (through thyroid-related genes and T3 levels) is highly active in males during the gonadal development in medaka (Oryzias latipes). Similarly, T3 treatments promoted female-to-male sex reversal in XX embryos. Subsequently, embryonic exposure to temperature-induced stress up-regulated the genes related to the thyroid and stress axes with a fnal increase in T3 levels. In this context, we show that blocking the stress axis response by the loss of function of the corticotropin-releasing hormone receptors suppresses thyroid-stimulating hormone expression, therefore, heat-induced activation of the thyroid axis. Thus, our data showed that early activation of the stress axis and, in consequence, the TH axis, too, leaves us with that both being important endocrine players in inducing female-to-male reversal, which can help predict possible upcoming physiological impacts of global warming on fsh populations.